(4x+9)+(4x+8)+(4x)=(4x)+(4x)+(5x+12)

Simple and best practice solution for (4x+9)+(4x+8)+(4x)=(4x)+(4x)+(5x+12) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4x+9)+(4x+8)+(4x)=(4x)+(4x)+(5x+12) equation:



(4x+9)+(4x+8)+(4x)=(4x)+(4x)+(5x+12)
We move all terms to the left:
(4x+9)+(4x+8)+(4x)-((4x)+(4x)+(5x+12))=0
We add all the numbers together, and all the variables
4x+(4x+9)+(4x+8)-(4x+4x+(5x+12))=0
We get rid of parentheses
4x+4x+4x-(4x+4x+(5x+12))+9+8=0
We calculate terms in parentheses: -(4x+4x+(5x+12)), so:
4x+4x+(5x+12)
We add all the numbers together, and all the variables
8x+(5x+12)
We get rid of parentheses
8x+5x+12
We add all the numbers together, and all the variables
13x+12
Back to the equation:
-(13x+12)
We add all the numbers together, and all the variables
12x-(13x+12)+17=0
We get rid of parentheses
12x-13x-12+17=0
We add all the numbers together, and all the variables
-1x+5=0
We move all terms containing x to the left, all other terms to the right
-x=-5
x=-5/-1
x=+5

See similar equations:

| 2(11/8y)+2y=190 | | -2(q+4)=-4 | | -2+a=18 | | x=48/2/3 | | -2x^2-8x-10=1011 | | 5.29-2.1r=8.51-1.9r | | 3x-45=17x+40 | | (7z-5)^-2/3-4(7z-5)^-5/3=0 | | (-4x)-7=15 | | 7(x-2)+3x=45 | | 2(s+6)+4s=102 | | m-17=-6 | | 2x^-20=5x-12 | | -6x2+60x-144=0 | | (2x+18)/x-1=x | | 5x-1(3x+1)=7 | | -8.2+t/2=1.7 | | e÷7.4=6.9 | | 12n+18+4n=-32 | | 10w+14=-11+6+11w | | 6n-2(n-2)=-11 | | 1.88x-6=0.58 | | 10=(d-2)/3 | | 1/3x+6=1 | | 5m+19=4(3m+12)-1 | | 5/8+y=23/8 | | 2.5x+7.5/3-8=145 | | -20g+10=-18g | | 14 + 9 = 2x2–7x x x–7 | | 2(2d+5+d)=0 | | 165+12p-5p=65+12p-5p | | -17c+8+16=4-18c |

Equations solver categories